STRUCTURAL ANALYSIS AND TECTONOSTRATIGRAPHY OF BIAK BASIN, YAPEN STRAIT, WEST PAPUA - Kasyfi Tahrizi, Muhammad
Biak Basin is a back-arc basin formed as a result of interaction between Australian Plate and Pacific Plate which still active currently. This study aims to determine the condition of the subsurface structure, the tectonostratigraphy of the research area, and the formation of the basin. The dataset used in this research consist of 2D seismic line, three well data, and checkshot. The method used in this research includes division of tectonostratigraphic units, structural analysis on seismic cross section, time structure map analysis, isochrone map analysis, and structural pattern analysis. The results of structural analysis show that the history of the formation of the Biak Basin includes a contractional phase (Pre-Pliocene) and a transtensional phase (Pliocene – Resen). Pre-Pliocene rocks act as bedrock of the Biak Basin which was formed in the contractional deformation phase in subduction tectonic episodes (Eosen – Oligocene and Late Oligocene – Late Miocene) and collision (Late Miocene) which is characterized by thrust fault and folds. The transtensional phase is divided into two based on its geometry and its relation to tectonic events. The Pliocene transtension phase produces a dextral strike slip fault with a northwestsoutheast trend, the Biak Fault Zone, and normal faults with a northeast-southwest trend forming a fault-wedge basin in the Pliocene. The Biak Fault Zone continues to develop and form a negative flower structure in the Pleistocene.